Analysis of the Influence of Knowledge Management on Innovative Work Behavior in Technology Companies - Akhmad Syafi’i; Shobichah Shobichah; Ginna Novarianti Dwi Putri Pramesti (Al-Makki Publisher, 2025)
In the knowledge-based economy, organizations increasingly rely on effective knowledge management to enhance innovation and maintain competitiveness. This study aims to analyze the influence of knowledge management on innovative work behavior among employees in technology companies. The research adopts a mixed approach by utilizing quantitative data collected through questionnaires distributed to employees and supported by qualitative insights from interviews and observations. The respondents consisted of 30 participants, including managerial staff and employees involved in knowledge-sharing and innovation-related activities. The findings indicate that knowledge management practices, particularly knowledge sharing, knowledge accessibility, organizational learning, and knowledge documentation, have a positive influence on employees’ innovative work behavior. Employees who actively participate in knowledge exchange activities demonstrate a higher tendency to generate, promote, and implement innovative ideas within their work environment. The results also highlight that leadership support and organizational culture play a significant role in strengthening the effectiveness of knowledge management practices. Organizations that foster collaborative learning environments and provide access to knowledge resources are more likely to encourage innovation among employees. These findings suggest that effective knowledge management systems can enhance both individual creativity and organizational innovation capacity. Therefore, technology companies are encouraged to develop structured knowledge management strategies and promote a knowledge-sharing culture to support sustainable innovation and improve organizational competitiveness in the digital era.